Role of Dendritic Epidermal T Cells in Cutaneous Carcinoma - Xiang, Jian; Qiu, Minghui; Zhang, Hongyi (Frontiers in Immunology, 2020)
Dendritic epidermal T cells (DETCs) are γδ T cells expressing invariant Vγ5Vδ1 T cell receptor (TCR) in murine epidermis. Initially, the development and the maturation of DETC progenitors are mediated by skint-1, TCR, and cytokines in the fetal thymus. Then, the DETC progenitors migrate to the epidermis with the guidance of selectins, CCR10, CCR4, etc. Eventually, mature DETCs proliferate and maintain a homeostatic population in the epidermis through IL-15 and aryl hydro-carbon receptor signaling. In “stressed” skin, DETCs are activated, exhibiting features such as a round morphology, cytotoxicity, and production of cytokines. In cutaneous carcinoma, DETCs generally inhibit tumor development directly in non-major histocompatibility complex-restricted manner, with the assistance of cytokines. DETCs also recognize and inhibit tumor via TCR, non-TCR receptors (such as 2B4 and NKG2D), or both. This study summarizes the biogenesis and the function of DETCs in cutaneous carcinoma and clarifies the essential surveillance role in the epidermis that DETCs play. As there are no DETCs in human epidermis but only human epidermis γδ T cells, we need to understand the anti-tumor pathways used by DETCs to find analogous immune pathways in human skin, which could be exploited for novel therapeutics.